Maintenance energy requirements in miniature colony dogs. Issue 1 (2nd May 2013) - Serisier, S.; Weber, M.; Feugier, A.; Fardet, M.‐O.; Garnier, F.; Biourge, V.; German, A. J.
Summary: There are numerous reports of maintenance energy requirements (MER) in dogs, but little information is available about energy requirements of miniature dog breeds. In this prospective, observational, cohort study, we aimed to determine MER in dogs from a number of miniature breeds and to determine which factors were associated with it. Forty‐two dogs participated in the study. MER was calculated by determining daily energy intake (EI) during a period of 196 days (28–359 days) when body weight did not change significantly (e.g. ±2% in 12 weeks). Estimated median MER was 473 kJ/kg 0.75 /day (285–766 kJ/kg 0.75 /day), that is, median 113 kcal/kg 0.75 /day (68–183 kcal/kg 0.75 /day). In the obese dogs that lost weight, median MER after weight loss was completed was 360 kJ/kg 0.75 /day (285–515 kJ/kg 0.75 /day), that is, 86 kcal/kg 0.75 /day, (68–123 kcal/kg 0.75 /day). Simple linear regression analysis suggested that three breeds (e.g. Chihuahua, p = 0.002; Yorkshire terrier, p = 0.039; dachshund, p = 0.035) had an effect on MER. In addition to breed, simple linear regression revealed that neuter status (p  =  0.079) and having previously been overweight (p = 0.002) were also of significance. However, with multiple linear regression analysis, only previous overweight status (MER less in dogs previously overweight p = 0.008) and breed (MER greater in Yorkshire terriers [p = 0.029] and less in Chihuahuas [p  =  0.089]) remained in the final model. This study is the first to estimate MER in dogs of miniature breeds. Although further information from pet dogs is now needed, the current work will be useful for setting energy and nutrient requirement in such dogs for the future.